2011
DOI: 10.1525/auk.2011.10240
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moisture and Food Supply on the Movement Dynamics of a Nonbreeding Migratory Bird (Parkesia noveboracensis) in a Seasonal Landscape

Abstract: We radiotracked Northern Waterthrushes (Parkesia noveboracensis) in four habitats in Puerto Rico during two winters (i.e., January-April) in 2003 and 2004 to determine the ecological determinants of diurnal space use and overwinter sitepersistence in this species. The majority of birds (69%) were sedentary and used a contiguous area within a single habitat over the winter period. A smaller percentage (31%) initially used a contiguous area within a single habitat but then permanently moved from that area to ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
1
18
1
Order By: Relevance
“…The marked emigrants we relocated at other study sites after site shifts within a winter were found to have moved from sites with low food resources to sites with higher food resources (i.e., significant for ripe fruit, marginally significant for ground arthropods), as expected for birds tracking ephemeral food resources (Sherry and Holmes 1996). These site shifts in response to food-resource declines are similar to the itinerant movements of Northern Waterthrushes (Parkesia noveboracensis) as they track changes in food resources at different sites associated with differential changes in moisture as the winter becomes drier (Smith et al 2010(Smith et al , 2011a. Although the moisture gradients among habitat patches used by warblers on Eleuthera are not as steep as the gradients encountered by wintering Northern Waterthrushes (i.e., dry forest to mangroves) and fruiting phenology may be out of phase with moisture availability (e.g., fruiting phase terminates as rainfall arrives), the itinerant patterns of response to habitat change in a heterogeneous landscape appear to be similar in the two species.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The marked emigrants we relocated at other study sites after site shifts within a winter were found to have moved from sites with low food resources to sites with higher food resources (i.e., significant for ripe fruit, marginally significant for ground arthropods), as expected for birds tracking ephemeral food resources (Sherry and Holmes 1996). These site shifts in response to food-resource declines are similar to the itinerant movements of Northern Waterthrushes (Parkesia noveboracensis) as they track changes in food resources at different sites associated with differential changes in moisture as the winter becomes drier (Smith et al 2010(Smith et al , 2011a. Although the moisture gradients among habitat patches used by warblers on Eleuthera are not as steep as the gradients encountered by wintering Northern Waterthrushes (i.e., dry forest to mangroves) and fruiting phenology may be out of phase with moisture availability (e.g., fruiting phase terminates as rainfall arrives), the itinerant patterns of response to habitat change in a heterogeneous landscape appear to be similar in the two species.…”
Section: Discussionmentioning
confidence: 64%
“…Experience, perhaps due to familiarity with a food source or shrub species and their locations, may enable adults to obtain asynchronously produced fruit shortly upon ripening more consistently than juveniles, while reducing the standing crop available to less experienced birds. In addition, familiarity with locations of widely scattered rich food patches obtained in the previous winter(s) may also give experienced birds an advantage (Smith et al 2011a), especially in late winter of dry years. Consistent with this scenario was an instance in which an individual (OO-XO) used the same disjunct site each winter (DD site in early winter and midwinter, and then shifted 5.1 km to the GF site in late winter in both 2005-2006 and 2006-2007), which suggests year-to-year stability of movement patterns, at least while resources varied consistently within winters.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because mangroves and cienagas retain more moisture while soils and vegetation in secondary forests and freshwater wetlands dry out, leaving fewer resources (i.e., phytophagous and aquatic emergent arthropods) for birds occupying those habitats (Smith et al, 2011). This is likely because mangroves and cienagas retain more moisture while soils and vegetation in secondary forests and freshwater wetlands dry out, leaving fewer resources (i.e., phytophagous and aquatic emergent arthropods) for birds occupying those habitats (Smith et al, 2011).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Many species of migratory birds occupy mangrove and lowland riparian tropical forests during the overwintering period, as they tend to have higher prey abundance than drier habitats (e.g., Chan, Yu, Zhang, & Dudgeon, 2008;Smith, Reitsma, & Marra, 2011;Wunderle, Lebow, White, Currie, & Ewert, 2014). Conservation of migratory species is challenging because their shifting distributions make it difficult to identify the potentially diverse factors limiting populations at different points throughout the annual cycle (Marra, Cohen, Loss, Rutter, & Tonra, 2015;Runge, Martin, Possingham, Willis, & Fuller, 2014;Webster, Marra, Haig, Bensch, & Holmes, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation